The Association Between Knee Osteoarthritis Risk Factors and Quality of Life Among Patients with Knee Osteoarthritis in Ubung Village - I Gusti Agung Bagus Arya Wiradarma; Gede Kambayana; Pande Ketut Kurniari; Dewa Ayu Kartika Tejawati; Sandra Surya Rini (PT Dexa Medica, 2026)
Osteoarthritis is a degenerative joint disease that affects the synovial membrane, cartilage, ligaments, and bones. Several risk factors for osteoarthritis include increasing age, family history of generalized osteoarthritis, heavy physical activity, obesity, and previous joint trauma or deformity. This study aimed to identify the knee osteoarthritis risk factors associated with patients’ quality of life. A cross-sectional study was conducted among 91 patients with knee osteoarthritis in Ubung Village, Denpasar City. Data were collected using the Short Form-36 (SF-36) questionnaire to assess the quality of life of the patients. Body weight was measured using a weighing scale, and height was measured using a stadiometer to determine body mass index (BMI). The results showed that several factors were significantly associated with poor quality of life among patients with knee osteoarthritis in Ubung Village, including age >60 years (odds ratio [OR]=4.331), female sex (OR=5.571), excess body weight (OR=7.353), and vigorous physical activity (OR=3.368). Overall, 73.6% of patients demonstrated a good quality of life. However, domain-specific analysis revealed moderate to low median scores in several components, including work limitations due to physical health disorders, pain, and general health. Bivariate analysis furtherdemonstrated that age >60 years, female sex, overweight or obesity status (BMI >23 kg/m²), occupations involving heavy physical activity, and a history of knee trauma were significantly associated with poor quality of life.